2019
DOI: 10.2503/hortj.utd-098
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of UDP:flavonoid 3-<i>O</i>-glycosyltransferase (UFGT)-like Genes and Expression Analysis of Genes Associated with Anthocyanin Accumulation in Mango ‘Irwin’ skin

Abstract: The red coloration of the mango 'Irwin' skin is an important factor determining its value in the Japanese domestic luxury fruit market. In the present study, to investigate the molecular mechanism underlying anthocyanin biosynthesis of mango fruit skin, UFGT-like genes were isolated and the expression profile of anthocyanin-related genes was determined. Several UFGT-like genes were identified in transcriptome data of red 'Irwin' mango skin and two genes, MiUFGT1 and MiUFGT3, were considered to be involved in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…In conclusion, MiUFGalT3, which was referred to as MiUFGT3 in our previous study (Kanzaki et al, 2019), was found to have relatively high galactosyltransferase activity. Considering the expression profile reported previously (Kanzaki et al, 2019) and its functional preference for UDP-galactose as a sugar donor, MiUFGalT3 rather than MiUFGT1 plays a crucial role in the light-induced red coloration of the mango fruit skin. Our findings may provide an important clue to elucidate the mechanism of anthocyanin accumulation in mango fruit skin.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…In conclusion, MiUFGalT3, which was referred to as MiUFGT3 in our previous study (Kanzaki et al, 2019), was found to have relatively high galactosyltransferase activity. Considering the expression profile reported previously (Kanzaki et al, 2019) and its functional preference for UDP-galactose as a sugar donor, MiUFGalT3 rather than MiUFGT1 plays a crucial role in the light-induced red coloration of the mango fruit skin. Our findings may provide an important clue to elucidate the mechanism of anthocyanin accumulation in mango fruit skin.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, VvGT5 and VvGT6, which share 91% amino acid sequence identity and are located in tandem on a chromosome different from that containing VvGT1, use UDP-glucuronic acid and UDP-Gal/Glc, as sugar donors, respectively, and use flavonols as acceptor substrates (Ono et al, 2010). In the present study, the function and biochemical nature of the two recombinant UFGTs were elucidated, but it is possible that other plant GTs such as MiUFGT4, which was isolated in our previous study (Kanzaki et al, 2019), contribute in part to the glycosylation of the diverse phenolic compounds in the mango peel (Berardini et al, 2005a). Further investigation is required to understand the divergence and division in the roles of glycosyltransferase family mem-bers in mangoes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Mango ( Mangifera indica L.) is the fifth most produced fruit crop worldwide ( ), which is widely cultivated in tropical and subtropical areas in the world. So far, the molecular mechanism of flavonoids biosynthesis in mango is mainly focusing on the expression changes of flavonoids biosynthetic genes and MBW complex by different treatments or in different cultivars ( Hoang et al., 2015 ; Kanzaki et al., 2019 ; Kanzaki et al., 2020 ), while how these genes are regulated by the up-stream TFs is still unknown. In the previous study, we found bagging treatment significantly decreased the anthocyanins and flavonols but surprisingly increased the proanthocyanidins accumulation in the fruit peel of red mango cultivar ‘Sensation’ ( Shi et al., 2021 ), which was very different from the other studies since light generally promotes all flavonoids compounds accumulation including flavonols, anthocyanins and proanthocyanidins ( Cortell and Kennedy, 2006 ; Li et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%